The Future of Indonesian Education: A Case Analysis on the Supply of High-Quality Teachers in Indonesia - Ferdina, Khansa Filza; Isnaini, Maya Hikmah; Arnoldi, Muhammad Daffa Tri (STAIRS: English Language Education Journal, 2024)
Despite continuous efforts to improve education, Indonesia still faces challenges such as unequal access to quality education, disparities in learning outcomes, and persistent teacher shortages. While the government has introduced professional development programs like Pengembangan Keprofesian Berkelanjutan (PKB) to enhance teacher quality, the effectiveness of these initiatives remains underexplored. This study aims to discuss the effectiveness of professional development programs in improving teacher competencies and addressing teacher shortages. This qualitative case analysis examines the challenges in the supply and quality of teachers in Indonesia, highlighting systemic issues and proposing a comprehensive approach to improve teacher qualifications, resource allocation, and policy implementation. The findings indicate that professional development programs significantly enhance both pedagogical and professional competencies, with blended learning models proving to be the most effective in supporting teacher development. However, challenges related to teacher recruitment and retention persist, particularly in replacing retiring educators. These results suggest the importance of continuous evaluation and adaptation of teacher development programs like PKB to sustain educational quality and effectively address teacher shortages across Indonesia.